Does end-tidal capnography confirm tracheal intubation in fresh-frozen cadavers?. Issue 5 (23rd September 2016) - Reid, Cliff; Ferguson, Ian; Burns, Brian; Habig, Karel; Shareef, Mohammed
Abstract : Background: Life-like end-tidal capnography (ETCO2 ) waveforms have been demonstrated in recently deceased and fresh-frozen cadavers following tracheal intubation, offering potential for high fidelity airway simulation training. As the mechanism for carbon dioxide production is not fully understood, it is possible that oesophageal intubation may also generate a capnograph. Our aim was to measure ETCO2 levels following (1) oesophageal and (2) tracheal intubation in fresh-frozen cadavers, and to observe the size, shape and duration of any capnographic waveform. Methods: Four fresh frozen cadavers underwent oesophageal intubation by an emergency medicine specialist with confirmation by a second specialist. Hand ventilation with room air via a self-inflating resuscitation bag was provided at 12 breaths per minute for 2 min or until ETCO2 was zero for 10 consecutive breaths. ETCO2 and waveform morphology were examined and video recorded. The oesophagus was then extubated and the process was repeated for tracheal intubation. Results: In no case was oesophageal ETCO2 detected. For two cadavers, life-like ETCO2 waveforms were achieved immediately after tracheal intubation, with maximum ETCO2 achieved by the second breath. In these cases waveform morphology was normal and persistent. Conclusions: Cadaveric oesophageal intubation did not result in a capnography waveform, simulating live patients. When present, ETCO2 following tracheal intubation showed normal morphology which was sustained for 2 min. However, ETCO2 was not present following tracheal intubation in all cadavers. These results represent instrumentation on the cadavers for the first time after thawing and further work should assess the repeatability of the findings with subsequent intubations.